Description of immatures of the genus Tropisternus Solier, subgenus Pristoternus Orchymont (Coleoptera: Hydrophilidae), with emphasis on the chaetotaxy and morphometry of larval forms - Torres, Patricia Laura Maria (2014)
The egg cases, larvae, and pupae of Tropisternus (Pristoternus) latus (Brullé, 1837), T. (P.) ovalis Castelnau, 1840, and T. (P.) laevis (Sturm, 1826) are illustrated and described for the first time. The egg cases are built with or without a mast, which can be ribbon-like or globular; all larval instars have seven anterior denticles in the anterior margin of nasale, and the antennal seta AN8 is present; the pupae bear 6 or 8 styli on the abdominal segments II–VI, the pleural styli can be either short or very long, and horn-like projections may be present on the abdominal segments II–VI. A comparison of the morphology of the egg cases, pupae and larval chaetotaxic and morphometric characters within the genus Tropisternus is presented.